Leadership Development Strategies in Organizations: The Role of Human Resource Management in Improving Effectiveness and Productivity - Ramles, Polin; Br Perangin Angin, Rosti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Effective human resource management strategies are key to sustainable business growth in a rapidly changing and competitive business environment. For organizations wishing to remain relevant and competitive in the global marketplace, the importance of leveraging innovation, environmental sustainability, and ethics and social responsibility in human resource management is of great concern. Therefore, the purpose of this research is to determine how the implementation of human resource management strategies that focus on innovation, sustainability, and ethics can help organizations achieve sustainable growth. This research was conducted using a descriptive-analytical approach by collecting data through literature review and content analysis of various relevant sources. The findings of this study revealed that HRM strategies based on innovation and sustainability help organizations to maximize human resource potential and create productive and sustainable work environments. In addition, the application of ethics and social responsibility in HR decision-making is a key pillar in creating an organizational culture of integrity. Organizations can achieve sustainable growth and sustainability by implementing this strategic approach.